Eighteen months in India, 1936-1937, being further essays and writings - Nehru, Jawaharlal, 1889-1964 (SAMP early 20th-century Indian books project ;, 1938)
Personal reactions of Jawaharlal Nehru, 1889-1964, freedom fighter and first prime minister of India.